Las Formas del Prima. Comprensión desde el psicoanálisis, las categorías de vida, muerte, crueldad y ambivalencia en la obra de Fiodor Dostoievsky. - Martínez Penagos, Paul Treicy (Universidad Antonio Nariño, 2021)
For the present investigation, the main objective was to understand the categories of life, death, cruelty and ambivalence seen in the works of Fyodor Dostoevsky. Thus, a categorical analysis was carried out which found distinctive characteristics that in turn have a certain unified content. However, it was possible to delimit them using documentary analysis, which contributed to the reconstruction of the aspects and dynamics in order to observe a particular reality in the study texts, taking the comprehensive and interpretive value of the Historical Hermeneutical approach. Thus, some Literary Analysis sheets were made together with a sheet that served as a scheme for the organization of citations for each category